Dendritic cells provide a therapeutic target for synthetic small molecule analogues of the parasitic worm product, ES-62 - Lumb, Felicity E. (Sci Rep, 2017)
ES-62, a glycoprotein secreted by the parasitic filarial nematode Acanthocheilonema viteae, subverts host immune responses towards anti-inflammatory phenotypes by virtue of covalently attached phosphorylcholine (PC). The PC dictates that ES-62 exhibits protection in murine models of inflammatory disease and hence a library of drug-like PC-based small molecule analogues (SMAs) was synthesised. Four sulfone-containing SMAs termed 11a, 11e, 11i and 12b were found to reduce mouse bone marrow-derived dendritic cell (DC) pathogen-associated molecular pattern (PAMP)-induced pro-inflammatory cytokine production, inhibit NF-κB p65 activation, and suppress LPS-induced up-regulation of CD40 and CD86. Active SMAs also resulted in a DC phenotype that exhibited reduced capacity to prime antigen (Ag)-specific IFN-γ production during co-culture with naïve transgenic TCR DO.11.10 T cells in vitro and reduced their ability, following adoptive transfer, to prime the expansion of Ag-specific T lymphocytes, specifically T(H)17 cells, in vivo. Consistent with this, mice receiving DCs treated with SMAs exhibited significantly reduced severity of collagen-induced arthritis and this was accompanied by a significant reduction in IL-17(+) cells in the draining lymph nodes. Collectively, these studies indicate that drug-like compounds that target DCs can be designed from parasitic worm products and demonstrate the potential for ES-62 SMA-based DC therapy in inflammatory disease.